Genetic variability and correlation studies in advanced breeding lines of soybean [Glycine max (L.) Merrill]: GENETIC VARIABILITY AND CORRELATION STUDIES IN ADVANCED BREEDING LINES OF SOYBEAN - ANJALI PAL; VEDNA KUMARI; RONIKA THAKUR; POONAM RANA (Journal of Oilseeds Research, 2024)
An experiment with 37 advanced breeding lines was conducted to study the genetic variability and association among seed yield and related traits along with direct and indirect effects in order to identify promising soybean genotypes. The genotypes were raised in randomized block design with three replications at experimental farm of department of genetics and plant breeding, CSKHPKV Palampur during kharif season under rainfed conditions. Analysis of variance revealed the presence of sufficient genetic variability for all the traits studied. High heritability coupled with high genetic advance was recorded for pod insertion height, plant height, branches per plant, 100-seed weight,seed yield per plant and pods per plant indicating the preponderance of additive gene action suggesting effective selection for these traits. Correlation coefficient analysis showed the significant and positive association of plant height, nodes on main stem, inter-node length, pods per plant, seeds per pod, biological yield per plant and harvest index with seed yield per plant both at phenotypic and genotypic levels. When the direct and indirect effects were estimated, the highest positive direct effect on seed yield per plant was exhibited by harvest index followed by biological yield per plant. Based on path coefficient analysis, harvest index and biological yield per plant could be considered as the direct selection indices for yield improvement in soybean.